Deciphering solar magnetic activity: some (unpopular) thoughts on the coupling of the Sun’s “weather” and “climate” - McIntosh, Scott W.; Leamon, Robert J. (Frontiers in Astronomy and Space Sciences, 2024)
The Sun exhibits episodic surges of magnetic activity across a range of temporal and spatial scales, the most prominent of which is the 11-th year modulation of sunspot production. Beside the ∼170 (min to max) decadal variation in sunspot production there is a less-explored quasi-annual variation in the range of 25–50 sunspots/year in magnitude. In addition, there is there is a slower, ∼80 year period, 10–50 variation in the sunspot number, that is commonly referred to as the “Gleissberg Cycle.” Using a suite of contemporary and historical observations we will illustrate these elements of our star’s episodic behavior and present a hypothesis that may provide a consistent physical link between the observed “climatic,” “decadal,” and “seasonal” magnetic variation of our star.